2021
DOI: 10.3390/s21206755
|View full text |Cite
|
Sign up to set email alerts
|

A Review: Application and Implementation of Optic Fibre Sensors for Gas Detection

Abstract: At the present time, there are major concerns regarding global warming and the possible catastrophic influence of greenhouse gases on climate change has spurred the research community to investigate and develop new gas-sensing methods and devices for remote and continuous sensing. Furthermore, there are a myriad of workplaces, such as petrochemical and pharmacological industries, where reliable remote gas tests are needed so that operatives have a safe working environment. The authors have concentrated their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 187 publications
(294 reference statements)
0
10
0
Order By: Relevance
“…Highlighted in the sections above, a vast array of traditional, novel, and hybrid complex materials have been uncovered and adopted within the frameworks of sensors dedicated toward detecting GHGs. These include the carbon nanomaterials, polymers, metal oxide semiconductors, and transition metal dichalcogenides, in calorimetric sensors; [102,108,117,122]] the solid polymer electrolytes, pseudo-solid-state electrolytes, and carbon materials, in electrochemical sensors; [67][68][69]109,121,133,137]] pyroelectric elements, LEDs, and PDs, in IR/FTIR/NDIR sensors; [72][73][74][75][76]78,84,85,109,131]] metal oxides, carbon materials, polymers, and single-or multi-mode optical fibers, in opticalbased sensors; [86][87][88][89][90][92][93][94]109,134]] piezoelectric materials, piezoceramics, carbon materials, and polymers, in acoustic/ultrasonic sensors; [91,[95][96][97][98][99]100,110,111] as well as polymer films in calorimetric or gas chromatographic sensors. [103,104,…”
Section: A Succinct Dictation Of Novel Materials In Ghg Sensingmentioning
confidence: 99%
“…Highlighted in the sections above, a vast array of traditional, novel, and hybrid complex materials have been uncovered and adopted within the frameworks of sensors dedicated toward detecting GHGs. These include the carbon nanomaterials, polymers, metal oxide semiconductors, and transition metal dichalcogenides, in calorimetric sensors; [102,108,117,122]] the solid polymer electrolytes, pseudo-solid-state electrolytes, and carbon materials, in electrochemical sensors; [67][68][69]109,121,133,137]] pyroelectric elements, LEDs, and PDs, in IR/FTIR/NDIR sensors; [72][73][74][75][76]78,84,85,109,131]] metal oxides, carbon materials, polymers, and single-or multi-mode optical fibers, in opticalbased sensors; [86][87][88][89][90][92][93][94]109,134]] piezoelectric materials, piezoceramics, carbon materials, and polymers, in acoustic/ultrasonic sensors; [91,[95][96][97][98][99]100,110,111] as well as polymer films in calorimetric or gas chromatographic sensors. [103,104,…”
Section: A Succinct Dictation Of Novel Materials In Ghg Sensingmentioning
confidence: 99%
“…Thus, part of the light transfers from core mode into cladding modes, and even escapes from the fiber in a radiative mode. [47] The cladding modes propagate backward and interfere with forward core modes, resulting in a series of peak drops in the transmission spectrum. The interference wavelengths can be written as: where n eff,core and n i eff ,clad are the effective RI of core mode and ith cladding mode, respectively.…”
Section: Grating Optical Fibers Gas Sensorsmentioning
confidence: 99%
“…Thus, part of the light transfers from core mode into cladding modes, and even escapes from the fiber in a radiative mode. [ 47 ] The cladding modes propagate backward and interfere with forward core modes, resulting in a series of peak drops in the transmission spectrum. The interference wavelengths can be written as: λBbadbreak=()neff,core+neff,cladinormalΛ/cosθ$$\begin{equation}{\lambda }_{\mathrm{B}} = \left( {{n}_{{\mathrm{eff}},{\mathrm{core}}} + {n}^i_{{\mathrm{eff}},{\mathrm{clad}}}} \right)\Lambda /\cos \theta \end{equation}$$where n eff,core and neff,cladi${n}^i_{{\mathrm{eff}},{\mathrm{clad}}}$ are the effective RI of core mode and i th cladding mode, respectively.…”
Section: Configurations and Mechanisms Of Optical Fiber‐based Gas Sen...mentioning
confidence: 99%
“…Various types of NH 3 sensors have been reported during the last decades [ 5 , 6 , 7 ]. Among them, due to the merits of small size, resistance to electromagnetic interference, and high sensitivity [ 8 ], optical fiber sensors have been widely studied in the field of gas sensing [ 9 , 10 , 11 , 12 ]. For instance, Xu et al [ 13 ] reported a highly sensitive NH 3 sensor by coating graphene oxide (GO)/cellulose acetate (CA) on the surface of a long-period fiber grating (LPFG).…”
Section: Introductionmentioning
confidence: 99%